Mild Coronavirus Disease 2019 (COVID-19) Is Marked by Systemic Oxidative Stress: A Pilot Study - Larissa E. van Eijk; Adriana Tami; Jan-Luuk Hillebrands; Wilfred F. A. den Dunnen; Martin H. de Borst; Peter H. J. van der Voort; Marian L. C. Bulthuis; Alida C. M. Veloo; Karin I. Wold; María F. Vincenti González; Bernardina T. F. van der Gun; Harry van Goor; et al. (Antioxidants, 2021)
Oxidative stress has been implicated to play a critical role in the pathophysiology of coronavirus disease 2019 (COVID-19) and may therefore be considered as a relevant therapeutic target. Serum free thiols (R-SH, sulfhydryl groups) comprise a robust marker of systemic oxidative stress, since they are readily oxidized by reactive oxygen species (ROS). In this study, serum free thiol concentrations were measured in hospitalized and non-hospitalized patients with COVID-19 and healthy controls and their associations with relevant clinical parameters were examined. Serum free thiol concentrations were measured colorimetrically (Ellman’s method) in 29 non-hospitalized COVID-19 subjects and 30 age-, sex-, and body-mass index (BMI)-matched healthy controls and analyzed for associations with clinical and biochemical disease parameters. Additional free thiol measurements were performed on seven serum samples from COVID-19 subjects who required hospitalization to examine their correlation with disease severity. Non-hospitalized subjects with COVID-19 had significantly lower concentrations of serum free thiols compared to healthy controls (p = 0.014), indicating oxidative stress. Serum free thiols were positively associated with albumin (St. β = 0.710, p < 0.001) and inversely associated with CRP (St. β = −0.434, p = 0.027), and showed significant discriminative ability to differentiate subjects with COVID-19 from healthy controls (AUC = 0.69, p = 0.011), which was slightly higher than the discriminative performance of CRP concentrations regarding COVID-19 diagnosis (AUC = 0.66, p = 0.042). This study concludes that systemic oxidative stress is increased in patients with COVID-19 compared with healthy controls. This opens an avenue of treatment options since free thiols are amenable to therapeutic modulation.